Eccentric exercise-induced muscle damage dissociates the lactate and gas exchange thresholds - Davies, R. C.; Rowlands, A. V.; Poole, D. C.; Jones, A.; Eston, R. G. (Journal of Sports Sciences, 2011)
We tested the hypothesis that exercise-induced muscle damage would increase the ventilatory ([Vdot] E) response to incremental/ramp cycle exercise (lower the gas exchange threshold) without altering the blood lactate profile, thereby dissociating the gas exchange and lactate thresholds. Ten physically active men completed maximal incremental cycle tests before (pre) and 48 h after (post) performing eccentric exercise comprising 100 squats. Pulmonary gas exchange was measured breath-by-breath and fingertip blood sampled at 1-min intervals for determination of blood lactate concentration. The gas exchange threshold occurred at a lower work rate (pre: 136 ± 27 W; post: 105 ± 19 W; P < 0.05) and oxygen uptake ([Vdot]O2) (pre: 1.58 ± 0.26 litres· min-1; post: 1.41 ± 0.14 litres · min-1; P < 0.05) after eccentric exercise. However, the lactate threshold occurred at a similar work rate (pre: 161 ± 19 W; post: 158 ± 22 W; P > 0.05) and [Vdot]O2 (pre: 1.90 ± 0.20 litres/min; post: 1.88 ± 0.15 litres/min; P > 0.05) after eccentric exercise. These findings demonstrate that exercise-induced muscle damage dissociates the [Vdot] E response to incremental/ramp exercise from the blood lactate response, indicating that [Vdot] E may be controlled by additional or altered neurogenic stimuli following eccentric exercise. Thus, due consideration of prior eccentric exercise should be made when using the gas exchange threshold to provide a non-invasive estimation of the lactate threshold.